Statistical methods in analyzing the shape of maxillary dental arches for dental applications / Norli Anida Abdullah - Norli Anida, Abdullah (2016)

(untitled)
This study aimed to propose shape features and statistical shape models to develop a novel shape discrimination procedure for the maxillary dental arch with important applications in dentistry. Standardized digital images of randomly selected dental casts were obtained and the image calibration and registration were attended to enable comparison of shape of the dental arches. A collective teeth positions from the digital images were proposed as a novel shape feature of the dental arch. Each tooth position is established from origin defined from stable anatomical landmarks. The mean shape category obtained from clustering method and the probability distribution of each shape category was further investigated to provide better statistical inference for the shape models of the dental arch. A modified COVRATIO statistics which incorporates the problem of small sample size and minimal model assumptions was then proposed as a discrimination method of shape and compared to the linear discrimination method. The proposed shape discrimination method was then used to determine suitable arch shape and indicate natural teeth positions. The results from this study show that multivariate normal and multivariate complex normal shape models together with the use of the proposed discrimination method can be used to discriminate shape of the dental arch. Consequently guides to determining suitable impression trays and predicting teeth positions for the edentulous patients (patients with all teeth missing) are provided. Verification of the proposed guides show that 91.42% of the sample studied indicates appropriate fitting to the resultant impression trays, and the original teeth positions (with an average error of 0.95 mm for each tooth position) were adequately estimated by 80% of the arches studied. The presented statistical methods may be beneficial in assisting inexperienced dentists and dental laboratory technicians to choose the most appropriate impression tray and to determine natural teeth positions for the Malaysian population.